Barriers to implementing environmental management accounting practices in small medium manufacturing companies in Malaysia - Mohamed, Rapiah; Zuriana Muhammad Jamil, Che. (International Journal of Engineering and Technology, 2018)
This study examines the barriers to adopting environmental management accounting among small-medium enterprises (SMEs) in Malaysia, specifically among manufacturing SMEs. The data were collected from SME managers using a mail survey. The data were analyzed using descriptive statistics, and the results showed that the financial barrier is the strongest barrier to practice environmental management accounting, followed by informational barrier, attitudinal barrier, institutional barrier, and management barrier. The results provide an understanding of SME managers concerning the reasons that hinder them from practicing environmental management accounting. In addition, the findings contribute to the body of knowledge on environmental management accounting as this area is considered to be a â€œgreen areaâ€ that requires more empirical evidence.Â Â